P011 Serum adhesion G protein coupled receptor levels are associated with disease activity in pediatric patients with Crohn's disease. (27th May 2021) - Werner, L; Weiss, B; Shamir, R; Shouval, D
Abstract: Background: Despite increasing number of therapies available for patients with Crohn's disease (CD), response rates are generally not high. Therefore, there is a great need to identify novel targets in patients with active disease. Methods: Serum samples were obtained from pediatric patients with CD at the time of diagnosis and following induction therapy with exclusive enteral nutrition (EEN) or anti-TNFa therapy, and from control subjects, defined as having normal colonoscopy without past or present history of inflammatory bowel diseases or other immune-mediated disorder. Associated clinical and laboratory data from these subjects was also collected. Serums were subjected to Olink technology (metabolism panel), based on proximity extension assay, enabling analysis of 92 proteins in each sample. Analysis was performed on a Normalized Protein eXpression (NPX) file comparing effect of different factors on the overall biomarker expression by supervised, multivariate, principal component analysis and verification by univariate ANOVA with Benjamini-Hochberg and post-hoc Tukey analysis. Results: Eighty-eight serum samples were collected: 30 from control subjects and 58 from 32 patients with CD. The median age of patients in the control and CD groups was 13.9 years (IQR 11.1–16.6) and 14.6 years (IQR 12.2–16.9), respectively (P=0.32). Twenty-four patients were treated with anti-TNFa agents and 8 with EEN. The median pediatric Crohn's Disease Activity Index decreased from 35 (22.5–42.5) to 5 (0–12.5, P<0.001) following induction therapy. We identified 34 proteins that significantly differed between patients and controls. Moreover, within patients with CD, 8/34 of these proteins were differentially expressed in patients with active or non-active disease. Among these, adhesion G-protein coupled receptors E2 (ADGRE2) and G2 (ADGRG2), important for macrophage differentiation, were significantly lower among CD patients vs. controls. When stratifying according to disease activity, low levels of both markers were identified in CD patients with active disease (either patients that were treatment-naïve or those with primary non-response to anti-TNFa therapy) or with increased CRP levels. Principal component analysis showed that a combination of ADGRE2 and ADGRG2 showed good separation between control subjects and treatment naïve patients with active CD. Conclusion: Serum levels of ADGRE2 and ADGRG2 are differentially regulated in patients with active CD, and should further be validated in additional Cohorts. The expression patterns and function of these receptors on different immune cells should be defined in future studies.